2012
DOI: 10.1002/cbdv.201100298
|View full text |Cite
|
Sign up to set email alerts
|

Specific DNA Duplex Formation at an Artificial Lipid Bilayer: towards a New DNA Biosensor Technology

Abstract: A novel technique is described which comprises a base-specific DNA duplex formation at a lipid bilayer-H(2) O-phase boundary layer. Two different probes of oligonucleotides both carrying a double-tailed lipid at the 5'-terminus were incorporated into stable artificial lipid bilayers separating two compartments (cis/trans-channel) of an optically transparent microfluidic sample carrier with perfusion capabilities. Both the cis- and trans-channels are filled with saline buffer. Injection of a cyanine-5-labeled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Experiment A: 4 + 5 + SG . In a preceeding manuscript we have studied the bilayer incorporation of the lipo-oligonucleotide 4 (5’-d( 1a -TAG GTC AAT ACT)-3’) and its successful and specific duplex formation with the cyanine-5-labeled complementary strand 5 (5’-d[(Cy5)-p-AGT ATT GAC CTA]-3’) [ 19 ]. As a negative control it had been shown that a membrane-bound duplex formation between the lipo-oligonucleotide 7 (5’-d( 1a -ATC CAG TTA TGA)-3’) and the oligomer 5 failed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Experiment A: 4 + 5 + SG . In a preceeding manuscript we have studied the bilayer incorporation of the lipo-oligonucleotide 4 (5’-d( 1a -TAG GTC AAT ACT)-3’) and its successful and specific duplex formation with the cyanine-5-labeled complementary strand 5 (5’-d[(Cy5)-p-AGT ATT GAC CTA]-3’) [ 19 ]. As a negative control it had been shown that a membrane-bound duplex formation between the lipo-oligonucleotide 7 (5’-d( 1a -ATC CAG TTA TGA)-3’) and the oligomer 5 failed.…”
Section: Resultsmentioning
confidence: 99%
“…In the first experiment (A) laser irradiation of the intercalated dye was performed at 470 nm. In orienting experiments Sybr Green I was irradiated at 470 nm, in order to see if this dye stains the complementary DNA strands 4 + 5 , which are known to form a duplex at the bilayer membrane [ 19 ]. Firstly, we evaluated the optimal measuring conditions such as the volume, the Sybr Green I concentration as well as of the lipo-oligonucleotides.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lipids are commonly used for modifying oligonucleotides. 10 The importance of such hybrid conjugates has been demonstrated in areas like nanobiotechnology, 11 cell biology 12 and medicine. 5 From a therapeutic point of view, lipid-oligonucleotide conjugates (LOCs) have emerged as an alternative to cationic particles in order to reduce toxicity and improve biodistribution.…”
Section: Introductionmentioning
confidence: 99%